Conservation Management Strategy for Water Resource Sustainability in Campus (International Journal of Scientific Research and Management (IJSRM), 2016)
Sustainability as a matter of fact has been an integral part of every step towards development of a town. Historical towns have developed in integration with sustainability when reviewed. Water Resource sustainability with its usage for habitation has been going critical day by day, where as availability of water is not at all a problem at most of the places and times. In campus planning sustainability in usage of water has observed a long way. There are some developments in town observed with leading approach to sustainability to make others to follow it. Authors have made an attempt to describe the water usage conservation management strategy at the educational institution campus analyzing the sustainability achievement during its usage. For that the authors have studie done such institutional campus in Nagpur District along with the residential facilities where water re source management was a challenge. It witnesses the thoughtful working on water sustainability aspects viz. reduce, reuse and recycle. The discipline of natural environment has inspired them to go in order definitely achieving the water resource sustainability.